Oxygen Consumption in South African Sauvignon Blanc Wines: Role of Glutathione, Sulphur Dioxide and Certain Phenolics - Fracassetti, D.; Coetzee, C.; Vanzo, A.; Ballabio, D.; du Toit, W.J. (South African Journal of Enology and Viticulture, 2016)
The aim of this research was to investigate the interaction between sulphur dioxide, glutathione (GSH) and certain phenols in the presence of oxygen in a synthetic wine and in clarified Sauvignon blanc wine. In this study, the clarified wine, from which most of the phenols had been removed, was compared to synthetic wine solution, with both mediums being enriched with caffeic acid to investigate the effect of different levels of sulphur dioxide and GSH on oxygen consumption. Moreover, thirteen young South African Sauvignon blanc wines with different levels of sulphur dioxide were oxygenated, and the oxygen consumption and phenolic and colour changes were monitored over time. The results show that oxygen consumption was influenced greatly by the presence of sulphur dioxide and, to a lesser extent, by the presence of GSH, with both compounds decreasing during the course of the experiment. During oxidation, an increase was observed in glutathionyl caffeic acid, as well as in oxidised glutathione (GSSG); however, this did not coincide with the percentage decrease in GSH. Oxidation further led to an increase in absorbance measurements at 420 and 440 nm (yellow-orange colour), which were reduced by the presence of SO2. A large variation was also observed in the oxygen consumption of the young wines, with this rate increasing with an increase in SO2 concentration. Positive correlations were also observed between oxygen, SO2, GSH and Cu concentrations, which were again negatively correlated with absorbance at 420 and 440 nm and GSSG concentrations.